Propaganda's Place in Strategic Communication: The Case of ISIL's Dabiq Magazine. Issue 3 (27th May 2017) - Wilbur, Douglas
ABSTRACT: This study explores how extremist groups use propaganda as a form of strategic communication. The theoretical foundation used was an adaption of neo-institutional theory for strategic communication. The sample was an issue of Dabiq, an online propaganda magazine, from the Islamic State in Iraq and the Levant (ISIL). The qualitative method employed was ethnographic content analysis. The study found ISIL used Dabiq as a form of strategic communication to achieve organizational goals in compliance with neo-institutional theory. Furthermore, ISIL used strategic communication in a similar manner as nonextremist groups; it sought to advance its organization as being superior to rival ones. These findings indicate that neo-institutional theory can further understanding of how extremist groups use propaganda, as strategic communication, to achieve organizational goals. This is accomplished by analyzing the functions specified in neo-institutional theory that propagandists attempt to fulfill. In general, this study offers evidence that the academic field of strategic communication offers significant potential to advance propaganda theory. If neo-institutional theory, as adapted for strategic communication, can explain and predict what a propagandist does, other strategic communication perspectives might offer the same ability to analyze propaganda and develop propaganda theory.